Surgeon volume and patient-reported urinary incontinence after radical prostatectomy. Population-based register study in Sweden. (2nd November 2022) - Arnsrud Godtman, Rebecka; Persson, Erik; Bergengren, Oskar; Carlsson, Stefan; Johansson, Eva; Robinsson, David; Hugosson, Jonas; Stattin, Pär
Abstract: Objective: To investigate the association between surgeon volume and urinary incontinence after radical prostatectomy. Methods: A total of 8326 men in The National Prostate Cancer Register of Sweden (NPCR) underwent robot-assisted radical prostatectomy (RARP) between 2017 and 2019 of whom 56% (4668/8 326) had responded to a questionnaire one year after RARP. The questionnaire included the question: 'How much urine leakage do you experience?' with the response alternatives 'Not at all', 'A little', defined as continence and 'Moderately', 'Much/Very much' as incontinence. Association between incontinence and mean number of RARPs/year/surgeon was analysed with multivariable logistic regression including age, Charlson Comorbidity Index (CCI), PSA, prostate volume, number of biopsy cores with cancer, cT stage, Gleason score, lymph node dissection, nerve sparing intent and response rate to the questionnaire. Results: 14% (659/4 668) of the men were incontinent one year after RARP. There was no statistically significant association between surgeon volume and incontinence. Older age (>75 years vs . < 65 years, OR 2.29 [95% CI 1.48–3.53]), higher CCI (CCI 2+ vs. CCI 0, OR 1.37 [95% CI 1.04–1.80]) and no nerve sparing intent (no vs . yes OR 1.53 [95% CI 1.26–1.85]) increased risk of incontinence. There were large differences in the proportion of incontinent men between surgeons with similar annual volumes, which remained after adjustment. Conclusions: The lack of association between surgeon volume and incontinence and the wide range in outcome between surgeons with similar volumes underline the importance of individual feedback to surgeons on functional results.